Trafficking in persons vis-à-vis the recent jurisprudence of the Inter-American Court of Human Rights: lessons for Brazil - Atchabahian, Ana Cláudia Ruy Cardia (New forms of human trafficking, 2024)
The present work aims to, starting from qualitative research based on primary and secondary sources’ document analysis, as well as the legal literature of international law and international human rights law, study the theme of human trafficking under the protective view of the Regional Human Rights Protection Systems, notably through a critical analysis of the recent decision produced by the Inter-American Court of Human Rights in the case of Fazenda Brasil Verde vs. Brazil to try to obtain grounds for comprehension of the subject in the international landscape and invoke the applicability of its conclusions to the national doctrine and jurisprudence.